Sensory neuron transient receptor potential vanilloid-1 channel regulates angiogenesis through CGRP in vivo - Zhu, Zhanfeng; Jiang, Yixuan; Li, Zixia; Du, Yu; Chen, Qinyi; Guo, Qiang; Ban, Yu; Gong, Ping (Frontiers in Bioengineering and Biotechnology, 2024)
Angiogenesis plays a key role in bone regeneration. The role of neurons of peripheral nerves involved in angiogenesis of bone defects needs to be explored. The transient receptor potential vanilloid 1 (TRPV1), a nociceptor of noxious stimuli, is expressed on sensory neurons. Apart from nociception, little is known about the role of sensory innervation in angiogenesis. Calcitonin gene-related peptide (CGRP), a neuropeptide secreted by sensory nerve terminals, has been associated with vascular regeneration. We characterized the reinnervation of vessels in bone repair and assessed the impact of TRPV1-CGRP signaling on early vascularization. We investigated the proangiogenic effect of neuronal TRPV1 in the mouse model of femur defect.TRPV1 activation enhanced angiogenesis by increasing vessel volume, number, and thickness. Meanwhile, TRPV1 activation upregulated the mRNA and protein expression of vascular endothelial growth factor A (VEGF-A), cell adhesion molecule-1 (CD31), and CGRP. Immunostaining revealed the colocalization of TRPV1 and CGRP in dorsal root ganglia (DRG) sensory neurons. By affecting neuronal TRPV1 channels, the release of neuronal and local CGRP was controlled. We demonstrated that TRPV1 influenced on blood vessel development by promoting CGRP release from sensory nerve terminals. Our results showed that neuronal TRPV1 played a crucial role in regulating angiogenesis during bone repair and provided important clinical implications for the development of novel therapeutic approaches for angiogenesis.